Altered N, P and C dynamics with absence of fire in Eucalyptus forests affected by premature decline. (16th March 2014) - Jones, Alan G.; Davidson, Neil J.
Abstract Absence of fire is increasingly recognized as an important driver of soil nutrient budgets in Eucalyptus forest, especially in forests affected by premature Eucalyptus decline, due to the effects of soil nutrient accumulation on nutrient balances and forest community dynamics. In this study, we present a dataset of soil and foliar nutrient analyses, and vegetation measurements from a fire chronosequence survey in native E. delegatensis forest. Measured indices include total soil and extractable soil nitrogen (N), or phosphorus (P), soil organic carbon (C), soil acid‐phosphatase (PME) activity, foliar N and foliar P, and understorey and overstorey vegetation canopy height. We show that in some cases indices are strongly linked to time since fire (2–46 years). Time since fire correlated positively with foliar N, total and extractable soil N, soil organic C, and also soil PME activity; the latter an indicator of biotic P demand. Differences in the strength of these relationships were apparent between two geology types, with stronger relationships on the potentially less‐fertile geology. The strong positive correlation with time since fire and understorey canopy height reflected increasing shrub biomass and thickening of the shrub layer. The strong positive correlation for soil or foliar N, but not P, with time since fire, indicates that P does not increase relative to N over time. P may, therefore, become limiting to growth in this plant community. Similarly, the significantly higher concentrations of soil N but not P, also found in both older and long‐unburnt forest stands (>100 years since management), may exacerbate a situation of soil nutrient limitation over several decades. A characteristic feature of long unmanaged stands is a developing tea tree (Leptospermum sp.) understorey, which may benefit from elevated soil N availability and increasing organic C accumulation with prolonged fire absence. This increased shrub biomass would outcompete Eucalyptus for resources, including soil nutrients and water.